Psychosocial Well-Being Determinants and Occupants’ Happiness in a Green Neighbourhood/Community - Ekhaese, Eghosa Noel; Hussain, Waqar Sukoon (Frontiers in Built Environment, 2022)
Abstract Psychosocial well-being and happiness are better in green neighbourhoods due to access to nature and green spaces. Hence, the study focus on investigating how psychosocial well-being determinants (PWDs) affect occupants’ happiness in a green residential community. The paper identifies the psychosocial-well-being domain, ascertains PWDs in the green neighbourhood, and analyse the effects of these PWDs on occupants'-happiness. The research method includes a qualitative, systematic subjective approach. Data were collected using triangulation - deductive extractions from literature to familiarise authors with the phenomenon under investigation, interviews guides and focused group discussion on expert opinions, and observations guide to elicit information on the identified PWDs in a green community. The researchers had interactions with fifty (50) professionals - Architects, Builders, Materials Engineers, Service Engineers, Estate surveyors, Urban and Regional Planners, Property developers, Medical Doctors, Psychologists, environmentalists, biologists, chemists, Art historians, environmental health practitioners and Occupants. From the interviews, discussion and deduction, psychosocial well-being determinants in a green neighbourhood include personal happiness and demography, lifestyle, community structure, local economy, activities, the built environment, natural environment, and global ecosystem. The data result suggested that other environmental factors influenced PWDs. Consequently, PWDs in the community affect occupants' well-being and happiness in a green home/neighbourhood or community.